English Teachers’ Practices on Pedagogical Well-being and Skills on Multiliteracy Pedagogy - Bastola, Ganesh Kumar (ILAM इलम, 2026)
The study examines the practices of secondary-level English teachers regarding pedagogical well-being and skills in multiliteracy pedagogy, in reference to the public school in Dharan Sub-Metropolitan. The teachers’ well-being and skills in multiliteracy pedagogy are assets that measure students’ reading strategies, analytical thinking, creativity, and critical thinking, among others, based on the students’ outcomes. This research was qualitative, and the prior design used here was a narrative inquiry. The prior source of the research data was obtained from five secondary-level English teachers of Dharan Sub-Metropolitan city. This research employed primary data, particularly from the secondary school and students studying in grades 9 to 12 in the secondary classroom. Classroom observation and interview were the tools to collect data. A closer reading of the narrative data indicated that each participant had different perceptions, experiences and practices. It was also noted that each teacher’s well-being was unique and versatile in their classroom engagement. The research found that teachers’ well-being requires in-depth knowledge of subject matter. They equally accepted that teachers’ well-being is to have appropriate knowledge and skills about managing materials and methodology. Furthermore, they believed teachers’ strong well-being is to have sound knowledge about technology; and to be able to make contextual use of the 21st century skills, including communication, collaboration, creativity and critical thinking. They equally provoked that teachers’ well-being is to being and becoming self-esteemed and retrospective in the classroom context.